Single Lithium‐ion Solid Conductors Based on Tetrazolate Anion and −Si−O− Species with Polyethylene Glycol Chains1. Issue 8 (18th April 2019) - Fei, Yuqing; Liu, Shimin; Long, Yan; Lu, Liujin; He, Yude; Ma, Xiangyuan; Deng, Youquan
Abstract: New organic‐inorganic hybrid single lithium‐ion (Li + ) conductors (SLICs) based on tetrazolate anion and −Si−O− species with polyethylene glycol (PEG) chains were developed using isocyanate as interim connection. The key design strategy is that the longer and freely movable wirelike PEG chain can improve Li + transfer in the presence of a high charge delocalized tetrazolate anion, and the −Si−O− species might improve the interfacial stability at the Li anode. FTIR, solid‐state NMR, XPS, XRD, BET, TGA, and DSC experiments were performed and the electrochemical properties were tested. The chemical structure and basic physicochemical properties were confirmed and revealed preliminarily. At 30 °C, a high enough conductivity (3.3×10 −6  S cm −1 ), Li + transference number (0.86), and wide electrochemical window (4.5 V) were obtained from the pure SLIC based on PEG with molecular weight of 600 g mol −1 . Besides, the developed SLICs displayed good interfacial compatibility with the Li metal electrode, as expected. Abstract : A new kind of organic‐inorganic hybrid single Li‐ion conductor (SLIC) is developed based on polyethylene glycol (PEG). It is tethered by lithium tetrazolate at one end and −Si−O− species at the other end. The freely movable PEG chain, combined with the tetrazolate anion, gives the SLIC a high conductivity while the bonded −Si−O− species ensures that it possesses high thermal and dimensional stabilities as well as interfacial stability and a high Li‐ion transference number.